A compact, stable, and angular independent dual‐band frequency‐selective surface for WiFi applications. Issue 10 (26th September 2018) - Ali, Haider; Shafique, Muhammad Farhan; Riaz, Laeeq; Khan, Mahmood Ashraf
Abstract: This research work reports on a compact dual‐band bandstop frequency‐selective surface design that is capable of suppressing signals in both 2.4 and 5 GHz bands. The structure is composed of closed loop topology with the unit element size of 0.084 λ0  × 0.084 λ0 . In addition to compactness, the proposed structure is independent of polarization defects and angular variations up to 45°. It suppresses signals at least by 15 dB in all polarizations and angle of incidences. The parametric optimization of unit cell allows accurate controlling of desired bands and bandwidth. A prototype of the proposed design is fabricated and measured and good agreement between measured and simulated results is demonstrated.